Rheumatic Heart Disease With NYHA Class Iii Heart Failure In Children: A Case Report - Darajat, Radya Adiwiguna; Perdiani, Agrippina; Putra, Handre; Satriani, Liku (Action Research Literate, 2025)
Rheumatic Heart Disease (RHD) is one of the serious complications of Acute Rheumatic Fever (ARF) which is still a major health problem, especially in developing countries. RHD can cause permanent damage to the heart valves, increasing the risk of heart failure in the pediatric population. This study aims to describe the clinical management of RHD cases with class III heart failure according to the New York Heart Association (NYHA) classification in a pediatric patient. The research method used a descriptive case study approach with a retrospective review of the medical records of a 13-year-old pediatric patient who experienced progressive dyspnea, fatigue, lower extremity edema, and intermittent fever. Physical and supporting examinations showed cardiomegaly, pulmonary edema, and severe mitral regurgitation. Management included administration of Benzathine Penicillin G, Prednisone 2 mg/kg/day, and other supportive therapies. The results showed significant clinical improvement within one week of treatment, with a long-term follow-up plan to prevent recurrence. The implications of this study emphasize the importance of early diagnosis and appropriate therapy to prevent the development of ARF into RHD and improve the long-term prognosis of pediatric patients. This study also highlights the need to increase public awareness and strengthen the primary health care system in early detection and management of RHD.